2019
DOI: 10.3389/fpls.2018.02004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Stress on Tissue Ultrastructure and Metabolite Profiles During Initiation of Radiata Pine Somatic Embryogenesis

Abstract: Climate change will inevitably lead to environmental variations, thus plant drought tolerance will be a determinant factor in the success of plantations and natural forestry recovery. Some metabolites, such as soluble carbohydrates and amino acids, have been described as being the key to both embryogenesis efficiency and abiotic stress response, contributing to phenotypic plasticity and the adaptive capacity of plants. For this reason, our main objectives were to evaluate if the temperature during embryonal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 79 publications
7
41
5
Order By: Relevance
“…In [2] they observed GDM rates lower than 5% in similar-aged EMs of radiata pine and results in Pinus nigra underlined that the formation of bipolar structures in EMs can only be obtained when 5mC levels are not higher than 18% [32]. Nonetheless, micromorphological analyses carried out in our laboratory confirmed the presence of polarised structures presenting different developmental and organizational stages under similar culture conditions in radiata pine [24].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In [2] they observed GDM rates lower than 5% in similar-aged EMs of radiata pine and results in Pinus nigra underlined that the formation of bipolar structures in EMs can only be obtained when 5mC levels are not higher than 18% [32]. Nonetheless, micromorphological analyses carried out in our laboratory confirmed the presence of polarised structures presenting different developmental and organizational stages under similar culture conditions in radiata pine [24].…”
Section: Discussionsupporting
confidence: 61%
“…Other studies have reported enhanced synthesis of this enzyme during heat stress in radiata pine and linked its accumulation with the production of secondary metabolites like flavonoids [59]. The presence of these last compounds was remarked in previous studies after heat exposure in EMs [24].…”
Section: Expression Pattern Of Stress-related Genesmentioning
confidence: 65%
“…In this strategy, high-abundance miRNAs in the HT-tolerant line, including the members of the miR160, miR167, and miR2949 families (ghr-novel-miR160b-5p > ghr-novel-miR160c-5p, ghr-miR167a > ghr-miR167b, and ghr-miR2949a-5p) were downregulated ( Figure 5), contributed to the accumulation of energy substances in cells, and ensured the proliferation of pollen mother cells. However, certain concentrations of secondary metabolites and fatty acids can increase the tolerance of cells to HT [32,33]. The SCP anthers suffered from HT stress, which can disturb cell energy metabolism and redox balance in the HT-sensitive line and eventually lead to male sterility.…”
Section: Different Mirna Families Temporally and Elaborately Regulatementioning
confidence: 99%
“…Meiosis is the period that is most sensitive to heat stress [39][40][41]. The accumulation of secondary metabolites in cells helps increase the heat tolerance of plants under HT stress [33,42]. Heat stress tolerance is a comprehensive process that requires multiple factors to achieve a dynamic balance.…”
Section: Different Mirna Families Temporally and Elaborately Regulatementioning
confidence: 99%
“…Furthermore, it is necessary to underline that the beneficial effects of BT in vivo are partially related to the temperature of the mineral water, while all the above-described in vitro studies have been performed at the physiological temperature of 37°C, because supraphysiological temperatures could represent a source of bias in terms of cell viability and metabolism (Castander-Olarieta et al 2019;Kaplan et al 2003;Mead et al 2012).…”
Section: Discussionmentioning
confidence: 99%